Infection of totally implantable venous access devices: A review of the literature. Issue 3 (May 2018) - Pinelli, Fulvio; Cecero, Elena; Degl'Innocenti, Dario; Selmi, Valentina; Giua, Rosa; Villa, Gianluca; Chelazzi, Cosimo; Romagnoli, Stefano; Pittiruti, Mauro
Totally implantable venous access devices, or ports, are essential in the therapeutic management of patients who require long-term intermittent intravenous therapy. Totally implantable venous access devices guarantee safe infusion of chemotherapy, blood transfusion, parenteral nutrition, as well as repeated blood samples. Minimizing the need for frequent vascular access, totally implantable venous access devices also improve the patient's quality of life. Nonetheless, totally implantable venous access devices are not free from complications. Among those, infection is the most relevant, affecting patients' morbidity and mortality—both in the hospital or outpatient setting—and increasing healthcare costs. Knowledge of pathogenesis and risk factors of totally implantable venous access device–related infections is crucial to prevent this condition by adopting proper insertion bundles and maintenance bundles based on the best available evidence. Early diagnosis and prompt treatment of infection are of paramount importance. As a totally implantable venous access device–related infection occurs, device removal or a conservative approach should be chosen in treating this complication. For both prevention and therapy, antimicrobial lock is a major matter of controversy and a promising field for future clinical studies. This article reviews current evidences in terms of epidemiology, pathogenesis and risk factors, diagnosis, prevention, and treatment of totally implantable venous access device–related infections.